2008
DOI: 10.1103/physrevlett.101.115003
|View full text |Cite
|
Sign up to set email alerts
|

Geodesic Acoustic Mode Induced by Toroidal Rotation in Tokamaks

Abstract: The effect of toroidal rotation on the geodesic acoustic mode (GAM) in a tokamak is studied. It is shown that, in addition to a small frequency upshift of the ordinary GAM, another GAM, with much lower frequency, is induced by the rotation. The new GAM appears as a consequence of the nonuniform plasma density and pressure created by the centrifugal force on the magnetic surfaces. Both GAMs in a rotating plasma are shown to exist both as continuum modes with finite mode numbers m and n at the rational surfaces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
101
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(110 citation statements)
references
References 25 publications
9
101
0
Order By: Relevance
“…[8] it was shown that continuum modes oscillating at the Brunt-Väisälä [9] frequency directly impacts the stabilily threshold of the internal kink mode, and that inconsistent treatment of the effect of toroidal rotation on the continuum mode would lead to erroneous results. The mode oscillating at the Brunt-Väisälä frequency is in fact a finite n zonal mode, which arises as one of two roots [10] from a dispersion relation that also defines the geodesic acoustic mode. In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…[8] it was shown that continuum modes oscillating at the Brunt-Väisälä [9] frequency directly impacts the stabilily threshold of the internal kink mode, and that inconsistent treatment of the effect of toroidal rotation on the continuum mode would lead to erroneous results. The mode oscillating at the Brunt-Väisälä frequency is in fact a finite n zonal mode, which arises as one of two roots [10] from a dispersion relation that also defines the geodesic acoustic mode. In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…According to Ref. [65], at the rational surface these frequencies are equal. 1 Repeating the procedure of Refs.…”
Section: A Torusmentioning
confidence: 97%
“…1) for isothermal magnetic surfaces, this result agrees with that of Refs. [44,65,47] for the low-frequency Alfvén continuum. In the limit f ?…”
Section: A Torusmentioning
confidence: 99%
“…͑13b͒ ͑for 1 Ͼ 0͒ of the GAM induced by the plasma rotation. 15 This frequency appears in the stability problem as a finite continuum frequency in the q Ϸ 1 layer, and it is this continuum frequency that, in a mathematical sense, is responsible for the stabilization seen in the examples discussed above. It is this stabilization that is interpreted as gyroscopic in Ref.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent paper, 15 the effect of the parametrization in Eq. ͑2a͒ for the continuous MHD spectrum of rotating plasmas was discussed, in particular the vanishing of the stabilizing continuum frequency in Eq.…”
Section: Introductionmentioning
confidence: 99%